Toxicity of Ashes Produced During the Combustion and Co-combustion of Coal and Meat and Bone Meal in a Fluidized- Bed Reactor - Barbosa, Rui (2009)
The replacement of fossil fuels by renewable fuels can contribute to improve the environmental performance of the power production and to move forward in the sustainability way. The experience has shown that the availability of alternative fuels can be an obstacle for its extensive use for energy production, since biomass is not always available. The use of non-hazardous wastes may be a good alternative to biomass, mainly if they are economically unattractive for recycling or if they present a high cost for land-filling. The co-firing of non-hazardous wastes with coal is, therefore, a subject of great interest for the sustainability of energy production and the reduction of the emissions of fossil greenhouse gases. The use of these wastes for energy is promising if they combine well with other fuels during the conversion process for energy production and have no negative effect on the combustion system, on the ash quality and on the gaseous emissions.